A Narrative Review of the Survival of the Coronavirus Family in Feces, Urine, and Wastewater - Seyedeh Fatemeh Mousavi; Fathollah Gholami-Borujeni (Hamadan University of Medical Sciences, 2022)
Wastewater is one of the most important ways of transmitting viral and bacterial pathogens that can cause nosocomial and clinical infections in humans. Although previous studies show that there is no current evidence that active coronaviruses are present in surface or ground waters or are transmitted through contaminated drinking water, there is an urgent need for more effective preventive measures to limit the spread of infection, which depends on understanding their routes of transmission and persistence in different environments. Here is a narrative review of the survival of the coronavirus family in feces, urine, and wastewater. Articles related to the presence of SARS-CoV-1 and SARS-CoV-2 in feces, urine, and wastewater and their survival time were searched in the literature. Articles published in the last decade (2000-2021) were selected based on the PRISMA method. The literature review showed that due to the high concentration of RNA virus in blood and urine samples with positive oral and anal swabs, no positive case has been reported using respiratory tests. The main findings of this review show that the maximum survival time of the SARS-CoV-2 in feces and urine was 33 and 31 days, respectively. Moreover, environmental conditions (temperature and pH) are the most important factors in the survival of SRRS-CoV in feces, urine, and wastewater. This study provides researchers with basic and useful information for future research orientations in relation to wastewater treatment plant systems to eliminate and manage emerging viral contaminants.